USING A GRAPH COLORING ALGORITHM TO DETERMINE THE ORDER OF GATHERING RADIATION MONITORING DATA FROM RENDEZVOUS POINTS OF A WIRELESS FLYING NETWORK - Fesenko, H. V.; Kliushnikov, I. M. (Systems and Technologies, 2018)
Wired networks, connecting monitoring stations (MS) of the automated radiation monitoring system (ARMS) to the crisis centre (CrS), can be damaged as a result of an NPP accident. To cope with the problem, an unmanned aerial vehicle (UAV)-enabled wireless network (UEWN), can be deployed. The aim of the paper is to develop an approach based on a graph coloring algorithm to determine the number of UAVs of an airplane-type and define the order of their use for gathering data from rendezvous points of a deployed UEWN during Zaporizhzhia NPP (ZNPP) post-accident monitoring missions. The existing graph coloring algorithms are analyzed and presented as a table. For later use, the greedy graph coloring algorithm based on bitwise operations on the adjacency matrix is ​​selected. A simplified scheme of deployment of a UEWN for transmitting the data from the MS to the CrS during NPP post-accident monitoring missions was developed and described. Two segments within the UEWN were considered: 1) Wi-Fi segment, comprising the WiFi equipment of the MS, the onboard WiFi equipment of the UAVs of a multi-rotor type (MUAVs), and onboard WiFi equipment of the UAV of an airplane-type (AUAV); 2) LoRaWAN segment, comprising the LoRaWAN equipment of the AUAV and the LoRaWAN equipment of the CrS. А scheme of UEWN subsystems deployment for the organization of data transfer between four monitoring stations of ARMS for ZNPP and rendezvous points in case of loss of wired networks. Using the selected graph coloring algorithm, it has been determined that three AUAVs are required for gathering and transmitting the data from four MSs to the CrS. Further studies should focus on investigating the effect of the location of the automatic battery replacement stations and their features on the UEWN’s functioning.